The Role of Political Leadership and Elites in the Russian Political System (2000-2025) - Doreen Benyamen Hermez (Genius Journals, 2025)
Vladimir Putin is one of the most influential leaders in Russian political life. Understanding the president's behavior plays a vital role in analyzing the trajectory of the Russian political system, especially since he has been considered a unique and influential leader in Russian politics since taking power in 2000. Putin's security environment is a major factor influencing the way he governs in Russia. The combination of his intelligence background, nationalist leanings, and strong personality directly influences his approach to political, economic, and social issues. In addition, Russia is distinguished by the presence of multi-level political elite, some of whom have stood by Putin and others who have opposed his policies. All of this has clearly indicated how he dealt with them and remained steadfast in power from 2000 until 2025.
Keywords: Political Leadership; Russian; Vladimir Putin